2016
DOI: 10.5194/hess-20-3167-2016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of satellite-based evapotranspiration estimates over the Tibetan Plateau

Abstract: Abstract. The Tibetan Plateau (TP) plays a major role in regional and global climate. The understanding of latent heat (LE) flux can help to better describe the complex mechanisms and interactions between land and atmosphere. Despite its importance, accurate estimation of evapotranspiration (ET) over the TP remains challenging. Satellite observations allow for ET estimation at high temporal and spatial scales. The purpose of this paper is to provide a detailed cross-comparison of existing ET products over the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 60 publications
1
12
1
Order By: Relevance
“…The mean annual ET was 543 mm during 1961-2010 in Zhang et al (2018) estimated by the advection-aridity model and was 378.1 mm during 1982-2012 in Wang et al (2018), which was retrieved by a modified Penman-Monteith-Leuning model. In contrast, the annual mean ET of our result was higher than the results from Peng et al (2016) who made a comparison of satellite-based ET and Zhang et al (2007) who estimated the ET based on the complementary hypothesis from Bouchet (1963). There are some reasons to explain this discrepancy.…”
Section: The Spatial-temporal Variations Of the Et Over The Tpcontrasting
confidence: 97%
“…The mean annual ET was 543 mm during 1961-2010 in Zhang et al (2018) estimated by the advection-aridity model and was 378.1 mm during 1982-2012 in Wang et al (2018), which was retrieved by a modified Penman-Monteith-Leuning model. In contrast, the annual mean ET of our result was higher than the results from Peng et al (2016) who made a comparison of satellite-based ET and Zhang et al (2007) who estimated the ET based on the complementary hypothesis from Bouchet (1963). There are some reasons to explain this discrepancy.…”
Section: The Spatial-temporal Variations Of the Et Over The Tpcontrasting
confidence: 97%
“…In addition, the annual cycle from LandFlux-EVAL in the Congo, presented in the current study, compares favorably to the annual cycles presented by Trambauer et al (2014). Furthermore, LandFlux-EVAL is believed to be a "best guess" estimate of evaporation (Peng et al, 2016), and has been used to evaluate CMIP5 models in previous studies (Mueller & Seneviratne, 2014). The above points strongly support using LandFlux-EVAL as an evaporation reference.…”
Section: Reference Data Setssupporting
confidence: 74%
“…Xu et al [30] found that ET showed a slight decreasing trend at the rate of 3.3 mm/decade from 2000 through 2014 in the TRHR by using an enhanced surface energy balance system (SEBS) algorithm. The simulated results were limited by the relatively short time span of the dataset and the uncertainties of model parameterization [31,32]. There are still large uncertainties about the spatiotemporal dynamics of ET over the complicated topography and heterogeneous surface of the TRHR.…”
Section: Introductionmentioning
confidence: 99%